Pengaruh Karakteristik Individu Dan Komunikasi Interpersonal Terhadap Kinerja Crew Kapal Di Bawah Management PT.APOL - Naufal Izzul Ihsan; Arika Palapa (Sekolah Tinggi Maritim Yogyakarta, 2022)
The development of human resources is stived to become a professional workforce because it is a source of driving wheels for the operational activities of a company. The presence of human resources is one of the most influential and particularl sources. The particularities that exist are different characters and performances. Differences in character can be a benchmark in the assessment of results and responsibilities. When the researchers did a fieldwork practicum in MV. URMILA, the ship was anchoring in Jakarta. There were differences in the character of each crew. Hence, the researcher chose “The Influence of Individual Characteristics on The Performance of the ship's crew under APOL company. The method employed in this study is a descriptive quantitative method, namely multiple linear regression analysis using SPSS, by distributing questionnaires with a total of 82 respondents whose ships are under APOL company management. The results of the regression calculation were indicators of Individual Characteristics of the performance of ship crews under APOL management with an effective contribution of 34.0% and interpersonal communication indicators affect the performance of the ship crew under APOL management was 8.8%. The results showed that individual characteristics have a significant effect on performance, interpersonal communication affects performance and the influence of individual characteristics and interpersonal communication affects the performance of ship crews under APOL management.